John Keats as a Critic: A New Approach - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education, 2021)
Romantic literary criticism in English literature is basically associated with and dominated by the writings of William Wordsworth in his ‘Preface to Lyrical Ballads’ (1800) and Coleridge in his ‘Biographia Literaria’. Apart from them, PB Shelly, Hazlitt, De Quincy and John Keats also contributed to the development of criticism in the Romantic period. How to cite this article: Priydarshi AK. John Keats as a Critic: A New Approach. J Adv Res Eng & Edu 2021; 6(4): 5-6. DOI: https://doi.org/10.24321/2456.4370.202107